Classical surgical approach and treatment with clips of extracranial internal carotid artery berry aneurysm - Haris Vukas (Journal of Health Sciences, 2016)
Introduction: We can define extracranial carotid artery aneurysm (ECAA) as bulb dilatation greater than 200% of the diameter of the internal carotid artery (ICA) or in a case of common carotid artery (CCA) greater than 150% of the diameter. Surgical intervention is required for the treatment of this disease.